Kang Q Huat receives Board of Engineers Malaysia President’s Academic Excellence Award - Noraini, Yusoff (UMPSA, 2024)
GAMBANG, 26 October 2024 – Bachelor of Civil Engineering with Honours graduate, Kang Q Huat, 24, never imagined he would be chosen as the recipient of the President’s Academic Excellence Award from the Board of Engineers Malaysia (BEM) during the 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).